2018
DOI: 10.1177/1471301218814641
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers’ involvement in decision-making processes regarding admission of persons with dementia to nursing homes

Abstract: The current Western health policy of ageing in place relies on a triad collaboration among patients, healthcare service providers and family caregivers. Such collaborations presuppose involvement in a vague juridical landscape. This article explores family caregivers' experiences with involvement in and influence on nursing home decision-making processes for persons with dementia. The data consist of twelve in-depth interviews with family caregivers. Using positioning theory, we demonstrate how family caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
12
1
2
Order By: Relevance
“…Unsurprisingly, we found that family was involved in 84% of the decisions of forced treatment and care, which is a legal requirement as well (34). Previous research has reported that family plays an important role in both the initiation and application of forced treatment and care (5,7,52). The degree of involvement of family varied across patients, and we found no significant differences in terms of family involvement among the cases where a PWD lived alone, with family, or in assisted housing.…”
Section: Types Of Decisionscontrasting
confidence: 53%
See 1 more Smart Citation
“…Unsurprisingly, we found that family was involved in 84% of the decisions of forced treatment and care, which is a legal requirement as well (34). Previous research has reported that family plays an important role in both the initiation and application of forced treatment and care (5,7,52). The degree of involvement of family varied across patients, and we found no significant differences in terms of family involvement among the cases where a PWD lived alone, with family, or in assisted housing.…”
Section: Types Of Decisionscontrasting
confidence: 53%
“…34 Previous research has reported that family plays an important role in both the initiation and application of forced treatment and care. 5,7,52 The degree of involvement of family varied across patients, and we found no significant differences in terms of family involvement among the cases where a PWD lived alone, with family, or in assisted housing. Our study did not shed light on the nature of relationship between the family members involved in a decision and the PWD in question.…”
Section: Involvement In Decisions Of Forced Treatment and Carementioning
confidence: 61%
“…Pårørendes omsorgsansvar er ikke nedfelt juridisk, men tidligere forskning viser at pårørende oppfatter at det sjelden er mulig å velge bort dette ansvaret (Larsen et al, 2018). Våre resultater viser at pårørendeansvaret medfører at pårørende setter egne behov på vent («Nå har jeg levd et «Alzheimerliv» så lenge at jeg lyst til å leve et vanlig liv, men hvordan kommer jeg dit?»).…”
Section: Mestringunclassified
“…Den samfunnsøkonomiske betydningen av uformell omsorg fra pårørende er derfor stor. Samtidig er pårørende utsatt for omfattende belastning, noe som er dokumentert i nasjonale og internasjonale studier (Chiao, Wu & Hsiao, 2015;Fonareva & Oken, 2014;Gilhooly et al, 2016;Larsen, Blix & Hamran, 2018). Kommunene er pålagt å tilby nødvendig pårørendestøtte i form av opplaering og veiledning, avlastningstiltak og omsorgsstønad til personer med saerlig tyngende omsorgsarbeid (Helse-og omsorgsdepartementet, 2017).…”
Section: Introduksjonunclassified
“…Current Norwegian policy aims to enable persons with dementia to live at home for as long as possible and to postpone residential care (Norwegian Ministry of Health and Care Services, 2012, 2015a, 2015b; a recent study revealed that Norwegian family caregivers contribute substantially to daily care and provide the larger share of care for home-dwelling persons with dementia (Vossius et al, 2015). Studies also indicate that family caregivers' own needs for help and support are substantial (Black et al, 2013;Larsen, Blix, & Hamran, 2018).…”
Section: Introductionmentioning
confidence: 99%